2022
DOI: 10.3390/nu14122399
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School-Based Nutrition Interventions on Parents and Other Family Members: A Systematic Literature Review

Abstract: Little is known about the impact of school-based nutrition interventions on parents and other family members. This systematic review aims to explore the impact of school-based nutrition interventions on different parental/family outcomes, mainly dietary intake, nutrition knowledge, and health outcomes. PubMed, Web of Science, PsycINFO, EconLit, Cochrane Reviews, and Google Scholar were systematically searched for controlled trials or natural experiments measuring the impact of school-based nutrition interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…One of the benefits of school-based health and nutrition education programmes is that children act to spread the information, bringing it to their homes to achieve transmission of the information to the whole family. 51,52 Our findings reveal the same with students discussing and sharing topics learnt with friends and families. However, to achieve better impact, studies recommend involvement of families and communities in the nutritional education programmes from the beginning.…”
Section: Interpretation (In Light Of Other Evidence)supporting
confidence: 59%
“…One of the benefits of school-based health and nutrition education programmes is that children act to spread the information, bringing it to their homes to achieve transmission of the information to the whole family. 51,52 Our findings reveal the same with students discussing and sharing topics learnt with friends and families. However, to achieve better impact, studies recommend involvement of families and communities in the nutritional education programmes from the beginning.…”
Section: Interpretation (In Light Of Other Evidence)supporting
confidence: 59%
“…Typically, many children’s PA and nutrition interventions occur in schools whereby children take part independently of their parents with the support of teachers. This more traditional approach often removes parents from the process, with parents receiving information from their children who have taken part perhaps in the form of leaflets or letters from schools where useful information may not subsequently be acted upon ( Spencer et al , 2018 ; Abderbwih et al , 2022 ). Notwithstanding, parents/guardians have been identified as one of five key stakeholders in the Creating Active Schools Framework (CAS; Daly-Smith et al , 2020 ) with acknowledgment of the role they play in supporting children to engage in extracurricular activities.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, systematic reviews have suggested that school-based interventions targeting PA, nutrition behaviours and obesity prevention can be more efficacious if a parental component is included ( Kitzman-Ulrich et al , 2010 ). Though, approaches to parental involvement in school-based interventions appear to be mixed and rely somewhat on information sent out to parents as opposed to direct involvement in activities ( Tomayko et al , 2021 ; Abderbwih et al , 2022 ). Such messaging can become problematic when it is at odds with the health-related beliefs and practices that children encounter at home, leaving parents feeling judged and discriminated against ( Spencer et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy and sustainable school meals together with food and nutrition education may provide a spill-over effect to the family or community [126]. For INSUM it seems beneficial to re-address the narrow way we look at the population of Eco-Regions.…”
Section: Study Population (Adolescents Children Adults Families)mentioning
confidence: 99%